Effects of sintering-resistance and large metal-support interface of alumina nanorod-stabilized Pt nanoparticle catalysts on the improved high temperature water gas shift reaction activity - Yati, Indri; Ridwan, Muhammad; Jeong, Go Een; Lee, Yunsu; Choi, Jae-Wook; Yoon, Chang Won; Suh, Dong Jin; Ha, Jeong-Myeong (ELSEVIER, 2014)
Pt nanoparticles stabilized with alumina nanorods (Pt@Al2O3) were synthesized by a simple preparation method using a mixture of Pt nanoparticles, an alumina precursor, an organic surfactant, and a reducing agent. Because the alumina nanorods stabilized Pt nanoparticles, the sintering of Pt nanoparticles was significantly suppressed during a high temperature water gas shift reaction, demonstrating 1.7-13.6 times higher CO conversions or 1.0-8.0 times higher TOF compared to other alumina-supported Pt catalysts. In addition, the increased metal-support interface for Pt@Al2O3 significantly improved the water gas shift reaction activity. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: GOLD